Simultaneous mapping of membrane voltage and calcium in zebrafish heart in vivo reveals chamber-specific developmental transitions in ionic currents - Hou, Jennifer H.; Kralj, Joel M.; Douglass, Adam D.; Engert, Florian; Cohen, Adam E. (Frontiers in Physiology, 2014)
The cardiac action potential (AP) and the consequent cytosolic Ca2+ transient are key indicators of cardiac function. Natural developmental processes, as well as many drugs and pathologies change the waveform, propagation, or variability (between cells or over time) of these parameters. Here we apply a genetically encoded dual-function calcium and voltage reporter (CaViar) to study the development of the zebrafish heart in vivo between 1.5 and 4 days post fertilization (dpf). We developed a high-sensitivity spinning disk confocal microscope and associated software for simultaneous three-dimensional optical mapping of voltage and calcium. We produced a transgenic zebrafish line expressing CaViar under control of the heart-specific cmlc2 promoter, and applied ion channel blockers at a series of developmental stages to map the maturation of the action potential in vivo. Early in development, the AP initiated via a calcium current through L-type calcium channels. Between 90 – 102 hours post fertilization (hpf), the ventricular AP switched to a sodium-driven upswing, while the atrial AP remained calcium driven. In the adult zebrafish heart, a sodium current drives the AP in both the atrium and ventricle. Simultaneous voltage and calcium imaging with genetically encoded reporters provides a new approach for monitoring cardiac development, and the effects of drugs on cardiac function.